Characteristics of peptones from grouper (Epinephelus fuscoguttatus) and parrotfish (Scarus javanicus) head by-products as bacterial culture media - Abdul Aziz Jaziri; Dwi Setijawati; Hefti Salis Yufidasari; Moh Dwi Pratomo; Dian W Wardani; Dinda Ersyah; Nurul Hudani Md Nawi (2020)
Peptones were extracted from the head by-products of grouper (Epinephelus fuscoguttatus) and parrotfish (Scarus javanicus) with different acid combinations. The peptones showed significant differences on yield, solubility, color, bacterial growth profile, and biomass production (P < 0.05). The yield of parrotfish peptone (PFP) and grouper fish peptone (GFP) ranged from 3.27% to 3.45% and 4.61% to 5.70%, respectively. The major component of both peptones was protein varied between 83.80% and 86.67%. The whiteness of peptone samples was in the range of 33.56% to 60.06% with the highest in GFP by adding 1.5% (v/m) of propionic/formic acid (1:2, v/v). Although the solubility of peptone samples was slightly lower than the commercial peptone, both PFP and GFP samples exhibited better performance in the growth of bacteria (Escherichia coli and Staphylococcus aureus). The biomass production of PFP and GFP increased significantly when compared that to commercial peptone. The PFP and GFP samples contained high values of the amino acids (glycine, glutamic acid, proline, and alanine). The results revealed that grouper and parrotfish head by-product are potential material for bacterial peptone.